Efektivitas Otomasi Administrasi Server Menggunakan Shell Script dan Cron Job pada Linux - Nicolas Elsada Lahagu; Leni Kartika Simbolon; Lotar Mateus Sinaga (UNIVERSITAS STEKOM, 2026)
Manual server administration introduces operational inefficiencies and elevated risks of human error. This study evaluated the effectiveness of server administration automation utilizing Shell scripting and Cron Job scheduling within a virtualized Linux Debian 12 environment. An experimental method compared manual execution against automated procesases based on execution duration, resource consumption, and error reduction. The findings indicated that the automated system executed backup routines within 0.043 seconds, demonstrating a 95.16% time efficiency increase compared to the manual baseline of 0.89 seconds. Automated monitoring maintained a stable resource allocation, utilizing 275 megabytes of memory and low central processing unit usage between 0.0% and 1.3%. Furthermore, automation reduced operational failures to 0%. In conclusion, this integration significantly optimizes server reliability.